2015
DOI: 10.1136/vr.102888
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antimicrobial resistance in faecal enterococci from vet‐visiting pets and assessment of risk factors

Abstract: The objective of this study was to determine the prevalence of antimicrobial resistance (AMR) exhibited by enterococci isolated from faeces of pets and its underlying risk factors. From September 2009 to May 2012, rectal swabs were collected from 74 dogs and 17 cats, selected from the population of animals visiting the Veterinary Hospital of University of Porto, UPVet, through a systematic random procedure. Animal owners answered a questionnaire about the risk factors that could influence the presence of AMR i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 35 publications
2
18
3
Order By: Relevance
“…In the present study, nearly half of the total isolates showed resistance to at least one antimicrobial. The positive correlation between the presence of AMR bacteria with previous antimicrobials used has been described previously [16]. A recent study suggested that dihydrostreptomycin is commonly used in Japanese TB racehorses [19].…”
Section: Discussionsupporting
confidence: 66%
“…In the present study, nearly half of the total isolates showed resistance to at least one antimicrobial. The positive correlation between the presence of AMR bacteria with previous antimicrobials used has been described previously [16]. A recent study suggested that dihydrostreptomycin is commonly used in Japanese TB racehorses [19].…”
Section: Discussionsupporting
confidence: 66%
“…The tetracycline resistance rate (99.6%) was higher than the one observed in most of the selected studies [6,[43][44][45][46][47][48], with the exception of the works presented by Iseppi et al [41] and Rodrigues et al [49], in which similar rates, of 97.5% and 95.2% respectively, were found. This antibiotic is also frequently one to which enterococci have the highest percentage of resistance, along with enrofloxacin [6,41,[43][44][45][46][47][48][49].…”
Section: Antimicrobial Susceptibility Testingmentioning
confidence: 55%
“…Disruption of the intestinal microbiota as a consequence of antibiotic use can lead to life‐threatening Clostridiodes difficile infections in humans 30 . Furthermore, antibiotic treatment leads to advantages in growth for resistant bacteria and provokes the development of new resistance mechanisms 31‐35 …”
Section: Introductionmentioning
confidence: 99%